IMMORTALITY, HUMAN NATURE, THE VALUE OF LIFE AND THE VALUE OF LIFE EXTENSION - Horrobin, Steven (Bioethics, 2006)
The emerging discourse concerning the desirability of intervention in senescence to achieve radical life extension for persons has featured some striking blurring in traditional liberal and conservative commitments and positions. This affords an opportunity for re-evaluation of these same. The canonical conservative view of the intrinsic value of life is re-examined and found primarily to involve a denial of human prerogative, rather than an active underwriting of the value of life extension. A critique is offered of an attempted argument against aging intervention from a proto-conservative worry about a purported threat to human nature. Immortality is found to be a red herring, but a revealing one. Further, the classic liberal view is examined and found wanting in terms of the gravity of its own commitment to, and fullness of its account of the value of life, and the value of life extension. An analysis of the liberal conception of personhood is proposed that both defines persons necessarily as processes, and demonstrates the inalienable quality of the value of life extension to persons so defined.